Strengthening Rural Healthcare: Comparative Innovations and Localized Strategies for Capacity Building - Fayaz Gul Mazloum Yar; Ezat Ullah Sail (Penerbit Hellow Pustaka, 2026)
The rural healthcare system in Afghanistan faces significant challenges, including limited access to services, workforce shortages, and inadequate infrastructure. This study explores innovative capacity-building approaches from India, Rwanda, and Bangladesh to identify strategies applicable to Afghanistan’s context. Using a mixed-methods approach, data were collected through surveys, interviews, and secondary analysis of healthcare indicators. Findings reveal that geographic isolation, gender disparities in the workforce, and resource deficiencies are critical barriers to effective healthcare delivery. Lessons from international case studies highlight the potential of community health worker programs, task-shifting strategies, and telemedicine solutions to address these challenges. Notably, 85% of stakeholders supported adapting task-shifting models, while 74% advocated for telemedicine integration to improve access in remote areas. This study contributes to the academic discourse on health systems strengthening by providing actionable recommendations tailored to Afghanistan’s socio-cultural and geographic realities. It emphasizes the importance of gender-inclusive policies, community engagement, and technology-driven solutions in creating a resilient rural healthcare system. The findings offer a roadmap for policymakers and practitioners to enhance healthcare access and equity in underserved regions